Biomarker Validation: Context and Complexities. Issue 3 (September 2019) - McShane, Lisa M.
Validation of a biomarker-based medical product development tool or clinical test is an evidentiary process that must be tailored to the proposed use. Appropriate data and analyses are needed to demonstrate that the bio-marker meets analytical and clinical performance criteria consistent with favorable benefit: risk balance.